2018
DOI: 10.1016/j.ajog.2017.10.040
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress-induced miR-27a targets the redox gene nuclear factor erythroid 2-related factor 2 in diabetic embryopathy

Abstract: Our study demonstrates that maternal diabetes-induced oxidative stress increases miR-27a, which, in turn, suppresses nuclear factor erythroid 2-related factor 2 and its responsive antioxidant enzymes, resulting in diabetic embryopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
30
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 81 publications
3
30
0
1
Order By: Relevance
“…The results of the reporter luciferase assay suggest that several miRNAs including miR‐27a, miR‐142‐5p, miR‐153, and miR128 are direct modulators of the Nrf2 . On the other hand, these miRNAs have been related to human diseases such as cancer and diabetes, but whether these miRNAs play an active role in the pathogenesis of NAFLD remains to be determined. In the present study, we provided the evidence that among four miRNAs studied, miR‐27a, miR‐142‐5p expression in liver cells were consistently associated with NAFLD, both in animal model and in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the reporter luciferase assay suggest that several miRNAs including miR‐27a, miR‐142‐5p, miR‐153, and miR128 are direct modulators of the Nrf2 . On the other hand, these miRNAs have been related to human diseases such as cancer and diabetes, but whether these miRNAs play an active role in the pathogenesis of NAFLD remains to be determined. In the present study, we provided the evidence that among four miRNAs studied, miR‐27a, miR‐142‐5p expression in liver cells were consistently associated with NAFLD, both in animal model and in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Various miRNAs including miR-7, miR27a, miR-34a and miR142-5p were reported to regulate the Nrf2-ARE pathway and glutathione homeostasis in the brain [36][37][38][39]. MiR-7 could increase the activity of Nrf2 and its downstream ARE, haeme oxygenase-1 (HO-1) and glutamate-cysteine ligase modifier subunit (GCLM), by repressing the inhibitor of Nrf2, Kelch-like ECH-associated protein 1 (Keap1) to exert cytoprotective effects in the brain [38].…”
Section: Discussionmentioning
confidence: 99%
“…2). These results are in who found that upregulation of miR-27a in hyperglycemia 13,41,42 . Administration of QC in both pure and conjugated forms significantly decreased miR-27a expression to control level, suggesting the anti-oxidant effect of QC by miRNA regulation.…”
Section: Discussionmentioning
confidence: 60%
“…microRNA-27a is one of the redox-sensitive microRNAs or "redoximiRs" which plays a direct role in the downregulation of Nrf2 and modulation of Nrf2-driven antioxidant gene expression. It has been shown that enhancement of miR-27a leads to suppression of Nrf2 and further, repression of Nrf2-controlled antioxidant genes in diabetic embryopathy 13 . In addition, it has been reported that upregulation microRNAs cause neurodegeneration by reducing the levels of Nrf2 14 .…”
mentioning
confidence: 99%